Kepuasan Pengguna Jasa Layanan Pembuatan Paspor di Kantor Imigrasi Kelas III Kota Bekasi - Mita Widyastuti; Irawati . (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2016)
The Momentum enactment of Law No. 25 of 2009 on Public Services showed the nation's attention to improve the delivery of public services public. One type is administrative services one of which is the passport. Immigration Office as an arm of the Ministry of Justice and Human Rights is often under scrutiny for its performance. Similarly, what happened on the service passport at the Immigration Office Class III Bekasi. A primary issue in this study is the quality of service of the Immigration Office Class III Bekasi. can not say either. This research is interesting to do given the same research ever conducted by Wicaksono (2012) in Class I Immigration Office Bandung. The results showed the gap between the expectations of respondents for the service passport by the Immigration officer Class I Bandung. By using the T test showed that there is no gap or difference between the services provided by the community expected. Thus, it can be said to be of service passports at the Immigration Office Class III Kota Bekasi satisfactory. These results are consistent with previous predictions given the improvements have been made related to service, after numerous public complaints leveled at the Immigration office. This indicates that the Immigration Office Class III Kota Bekasi responsive to the mandate contained in Law No. 25 of 2009 on Public Service